Kundur [Benincasa hispida (Thunb.) Cogn.]: A potential source for valuable nutrients and functional foods. - Saari, Nazamid; Abdul Hamid, Azizah; Mohd Zaini , Nurul Aqilah; Anwar, Farooq (Elsevier, 2011)
Kundur [Benincasa hispida (Thunb.) Cogn.], a member of the family Cucurbitaceae, is one of the famous crops that are grown primarily for its fruits and usually recognized with its nutritional and medicinal properties especially in Asian countries. Kundur fruit has been valued as a nutritious vegetable as it provides a good source for natural sugars, amino acids, organic acids, mineral elements and vitamins. A number of medicinal properties such as anti-diarrheal, anti-obesity, anti-ulcer, and antioxidant and diuretic have been ascribed to this fruit of high economic value. As a rich source of functionally important bioactives and therapeutics such as triterpenes, phenolics, sterols, and glycosides, the fruit has been widely used for the treatment of epilepsy, ulcer, and other nervous disorders in the native medicine system of Asia. This review focuses on the cultivation, nutritional and chemical composition, as well as medicinal and therapeutic properties of this multipurpose fruit, as one of the potential sources of bioactives for functional food and nutraceutical applications.